Obinutuzumab plus chlorambucil versus ibrutinib in previously untreated chronic lymphocytic leukemia patients without TP53 disruptions: A real-life CLL campus study - Visentin, Andrea; Mauro, Francesca Romana; Catania, Gioachino; Fresa, Alberto; Vitale, Candida; Sanna, Alessandro; Mattiello, Veronica; Cibien, Francesca; Sportoletti, Paolo; Gentile, Massimo; Rigolin, Gian Matteo; Quaglia, Francesca Maria; et al. (Frontiers in Oncology, 2022)
One of the main issues in the treatment of patients with chronic lymphocytic leukemia (CLL) deals with the choice between continuous or fixed-duration therapy. Continuous ibrutinib (IB), the first-in-class BTK inhibitor, and obinutuzumab-chlorambucil (G-CHL) are commonly used therapies for elderly and/or comorbid patients. No head-to-head comparison has been carried out. Within the Italian campus CLL network, we performed a retrospective study on CLL patients without TP53 disruption treated with IB or G-CHL as first-line therapy. Patients in the G-CHL arm had a higher CIRS score and the worst renal function. The overall response rates between the G-CHL and IB arms were similar, but more complete remissions (CRs) were achieved with G-CHL (p = 0.0029). After a median follow-up of 30 months, the progression-free survival (PFS, p = 0.0061) and time to next treatment (TTNT, p = 0.0043), but not overall survival (OS, p = 0.6642), were better with IB than with G-CHL. Similar results were found after propensity score matching and multivariate analysis. While PFS and TTNT were longer with IB than with G-CHL in IGHV unmutated patients (p = 0.0190 and 0.0137), they were superimposable for IGHV mutated patients (p = 0.1900 and 0.1380). In the G-CHL arm, the depth of response (79% vs. 68% vs. 38% for CR, PR and SD/PD; p < 0.0001) and measurable residual disease (MRD) influenced PFS (78% vs. 53% for undetectable MRD vs. detectable MRD, p = 0.0203). Hematological toxicities were common in the G-CHL arm, while IB was associated with higher costs. Although continuous IB provides better disease control in CLL, IGHV mutated patients and those achieving an undetectable MRD show a marked clinical and economic benefit from a fixed-duration obinutuzumab-based treatment.